Histological study on a novel bone graft substitute: Human derived tooth-hydroxyapatite compared with coralline hydroxyapatite - (:unkn) unknown (IEEE, 2001)
Different types of bone-graft substitutes have been developed, and are on the market worldwide to eliminate the drawbacks of autogenous grafting. They vary in composition, strength, osteoinductive and osteoconductive properties, mechanism and rates at which they are resorbed and remodelled. Of these, THA is a novel material produced by one of us (FNO). This study was performed to determine the histological properties of THA on animals, and to achieve this a standard on the market coralline HA (CHA) was used as control. 20 sheep were used in this study and divided into 2 groups. Human THA (Group-A) and CHA (Group-B) materials were implanted to the tibiae of 10 sheep in each group. The histological examinations of surrounding bone response of the implant materials were done 12 weeks after implantation. There was no significant difference histologically between groups A and B. All materials were found to be surrounded by new bone tissue. THA was found to be as efficient as standard CHA on histological basis. In addition, economical production of THA should be taken into consideration. In future, THA may be a viable alternative on bone grafting when clinical trials were completed.
Keywords: hydroxyapatite; grafting; bone graft; osteoconduction; BOVINE CANCELLOUS BONE; BIOMEDICAL APPLICATIONS; YIELD MATERIALS; IN-VITRO; OSTEOINDUCTIVITY; CERAMICS; MATRIX